Schöner wohnen wollen (sollen) - Riedel, Anna-Katharina (My University, 2018)
Not only can we live beautifully, living can be even more beautiful, that’s what the title of the most famous living magazine in German-speaking countries promises and demands. The editors point at the design of living by using a climax in the title, but furthermore, the focus is on optimizing the act of living. Living, shown in media like Schöner Wohnen, can be revealed as a sociopolitical act, which entangles subjectification, normalization and optimization processes. The cover sheets of Schöner Wohnen between 1980-1999 will be analyzed with regard to their image-text-combinations in order to identify the supposedly private space of living as a place of action for optimization and its representation. The discoursive links between social and political developments and the history of living in this period are specific interests of this article, as well as reflections on the magazine as a medium and its functional mechanisms.
Optimierung als Subjektivierungsweise auf den Titelblättern der Schöner Wohnen in den 1980er- und 1990er-Jahren
Keywords: 729 Entwurf, Gestaltung, Innenarchitektur